Desenvolvimento de modelo experimental de indução da obesidade em ratos wistar - Macêdo, Lano Ermenson Miranda (2016)
Introduction: Obesity is a chronic disease that affects approximately one third of the global population, this pathology is associated with various comorbidities, such as type 2 diabetes, hypertension, dyslipidemia, hepatic steatosis and behavioral disorders related to food intake, leading to decreased quality and the life expectancy of these patients. The most effective current treatment of these patients is the bariatric surgery. For the experimental study of obesity and its comorbidities are used animal models of obese rats and genetically modified diabetics, poor access and high costs. Objective: To develop an alternative experimental model of obesity in non-diabetic Wistar rats and non-genetically modified, simple and reproducible. Methods: We investigated the effects of diet-induced obesity in Wistar rats, male, divided in Group 1 – G1 (n = 10): control, fed with commercial feed and water ad libitum and Group 2 - G2 (n = 20) fed with high fat diet (HF-diet) + fructose 20% for 17 weeks. Will be evaluated growth parameters such as weight, Lee index and total body fat. They will also be analyzed glucose tolerance, plasma glucose, plasma triglycerides, total cholesterol levels and hepatic steatosis. Results: The rats of the HF-diet group showed a significant increase in abdominal circumference, Lee index and abdominal fat compared to the control group. HF diet effects on blood glucose levels are described discrepantly (G2: 259.53 ± 99.27 / G1: 146.50 ± 37.85), causing other metabolic abnormalities such as high levels cholesterol (G2: 161.76 ± 46.71 / G1: 112.32 ± 36, 43), HDL (G2: 47.65 ± 9.6 / G1: 70.47 ± 10.03), LDL (G2: 114.10 ± 44.80 / G1: 41.91 ± 28.88) and the liver function, alkaline phosphatase (G2: 44.31 ± 10.17 / G1: 28.52 ± 6.07), ALT (G2: 200.53 ± 84.56 / G1: 134.00 ± 40.00 ) and AST (G2: 240.62 ± 149.99 / G1: 55.61 ± 47.93). There were no changes in the weight of the animals and the naso-anal length compared the test group with the control group, were not evident differences in protein total (G2: 6.03 ± 1.18 / G1: 5.60 ± 1.83) and blood triglycerides (G2: 142.85 ± 114.23 / G1: 121.37 ± 66.85). Conclusion: The experimental model of obesity induction in Wistar rats by high fat diet and fructose demonstrated to be feasible and was able to develop the key clinical features of obesity in animals as well as biochemical changes lead to metabolic syndrome. Therefore, this model can be an alternative to setting up obese groups of animals used in further research on obesity and metabolic syndrome.